Types and costs of medications returned by outpatients at a Malaysian teachinghHospital: a one-year cross-sectional study - Jamalud-din, Nor Akilah; Tengku Mohd. Kamil, Tengku Karmila; Hu Wei Ying, Mery; Elnaem, Mohamed Hassan Abdelaziz; Ahmed, Abdulkareem Mohammed; Mohamed Nazar, Nor Ilyani; Mohd Taufek, Nor Hidayah (2022)
Introduction: Medication wastage is attributable to various factors, including therapeutic failure, over-prescription, and poor compliance. Data regarding the cost and types of returned medications are essential to estimate the financial burden that can be reduced locally through targeted intervention. This study aimed to investigate the types and cost of medications returned by outpatients at a teaching hospital in Kuantan, Pahang. Materials and methods: This cross-sectional study collected data from the electronic medical record based on the list of returned medications at the outpatient pharmacy department at Sultan Ahmad Shah medical Centre (SASMEC) @IIUM between January and December 2021. All medications with SASMEC patients' label were included. The medications were classified according to the classification index based on the British National Formulary. The data were analysed using Microsoft Excel version 16.52. The cost associated with returned medications was calculated, referring to the latest cost price of the respective medications. Results: A total of 134 patients returned their medications in 2021 (mean ± SD age: 63 ± 13 years), with 52% females. The total quantities of returned medications were 11,054 units. These included pills, devices (inhalers, insulin pens), bottles, and plastic containers. The overall cost of these medications was Ringgit Malaysia (RM) 13,594.90 (mean per patient: RM 101.45). The highest number of returned medications was from the cardiovascular group (32.5%), followed by the endocrine group (26%) and musculoskeletal group (11.9%). The highest cost for returned medications was the endocrine group (49%), followed by the cardiovascular group (20%) and the musculoskeletal group (10%). Conclusion: Medications used for cardiovascular diseases were the most frequently returned at outpatient pharmacy, whereas those for endocrine diseases contributed to the highest cost. Future research could focus on identifying modifiable factors that can contribute to the sustainability of health resources by reducing the cost of returned medications.